profile
Опубликовано - 2 дня назад | По предмету Математика | автор Аноним

Найдите p1(x) + p2(x) и p1(x)-p2(x),если p1(x)=2x^3-3x+1 p2(x)= -x^3-2x-1

  1. Ответ
    Ответ дан Lourdes
    p1(x) + p2(x) и p1(x) - p2(x), если p1(x) = 2x^3 - 3x + 1, p2(x)= -x^3 - 2x - 1;

    p1(x) + p2(x) = 2x^3 - 3x + 1 + (-x^3 - 2x - 1) = 2x^3 - 3x + 1 - x^3 - 2x - 1 = x^3 - 5x;

    p1(x) - p2(x) = 2x^3 - 3x + 1 - (-x^3 - 2x - 1) = 2x^3 - 3x + 1 + x^3 + 2x + 1 = 3x^3 - x + 2.
    0



Топ пользователи


Hekady (
206)
shozavitya (
180)
znanija (
172)
Eveline (
58)